T Cell Receptor Immune Repertoires Are Promptly Reconstituted After Methicillin-Resistant Staphylococcus aureus Infection - Liu, Jiangjun; Liu, Zhongqiang; Zhu, Yuanqi; Dong, Bingzi; Cai, Zheng; Liang, Qing; Wang, Kejia (Frontiers in Microbiology, 2019)
T cells represent a subset of lymphocytes characterized by immunosurveillance and immunoregulation function. Peripheral blood mononuclear cells (PBMCs) are enriched in T cells, which exert critical antimicrobial roles in infectious diseases. High-throughput sequencing of the T cell receptor (TCR) provides deep insight into monitoring the immune microenvironment. Flow cytometry was used to analyse the distribution of αβ/γδ T cells and their CD69, IFN-γ/IL-17 expression from PBMCs. Here, we utilized next-generation sequencing (NGS) to detect the complementarity determining region 3 (CDR3) of TCRβ (TRB) and TCRδ (TRD) chain after methicillin-resistant Staphylococcus aureus (MRSA) infection. Our data demonstrated a significant increase in the activation of αβ and γδ T cells after MRSA infection. Simultaneously, significantly high CDR3 amino acid (AA) diversity and markedly reconstituted TCR immune repertoires were observed after MRSA infection. Finally, we identified several MRSA-specific initial CDR3 AA motifs after MRSA infection. Our work reveals the profiles of TRB and TRD immune repertoires in response to MRSA and demonstrates a reconstitution of the TCR immune repertoire after MRSA infection.